Efektivitas Penggunaan Media Audio Visual terhadap Hasil Belajar Siswa pada Mata Pelajaran PAI di SMA Negeri 2 Lengayang - Putri, Frensiska Nendia; Nurjanah, Nurjanah (Lembaga Yasin AlSys, 2025)
The low academic achievement of students in Islamic Religious Education (PAI) at SMA Negeri 2 Lengayang, primarily due to a lack of interest in conventional lecture-based methods has highlighted the need for more interactive teaching strategies. This study aims to evaluate the effectiveness of audiovisual media in improving learning outcomes among Grade X Phase E students. A quantitative approach was employed using a quasi-experimental method with a nonequivalent control group design. The sample consisted of two classes: the experimental group used audiovisual media, while the control group received traditional lecture-based instruction. Data were collected using multiple-choice tests that had undergone validity and reliability testing. Analysis using an independent sample t-test revealed a significant difference between the two groups, with a significance value of p < 0.001. The average post-test score of the experimental group was 84.13, notably higher than the control group's 66.53. N-gain analysis showed a 59% improvement, indicating that audiovisual media is moderately effective in enhancing learning outcomes. The study concludes that audiovisual media is a viable instructional strategy for improving students' understanding and academic performance in PAI. The findings suggest that teachers should integrate educational technology to foster a more engaging and meaningful learning experience.